(3GdVeGfGJ GdJGOjHjI ddehXa GdYGe Ydi OhdI GdGeGQGJ GdYQHjI GdeJMOI (B: s (3OQGSI ebGQfI (B/ s - (3YHOGddg QGTO YHjO GdTGeSis; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3jYO GdJGOjH ai GdhXjaI GdYGeI OhQG gGeG ai GQSGA eHOG GdGfVHGW GdhGLH JhGaQg dJecjf GdGOGQI ef GdbjGe HeG jfGW HgG ef GOhGQ dJMbjb GdUGdM GdYGe (B: (3hgh HeKGHI hSjdI dYbGH GdehXa Ydi GdSdhc GdefMQa dSjQ GdeQGab GdYGeI HGfJXGe hGVWQGH hJYO GdVeGfGJ GdJGOjHjI UeUe GeGf ddefWb ebGHd SdWGJ GdGOGQI GdhGSYI (B: (3hPdc ef efWdb GdehRGfI Hjf eJWdHGJ eHOGF aGYdjI GdGOGA GdGOGQi haGYdjI GdeMGSHI GdhXjajI haGYdjI GdTQYjI GdGOGQjI (B.s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2007s
(3HHdjhLQGajG(B: (3UaMGJ (B185-197s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdGeGQGJ GdYQHjIs; (3GdVeGfGJ GdJGOjHjIs; (3GdehXa GdYGes; (3eQMdI GdJMbjbs; (3eQMdI JhbjY GdLRGA GdJCOjHis; (3eQMdI GdeMGceIs; (3GdVeGfGJ GdTcdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes